Asymmetric dihydroxylation route towards the synthesis of (R)-clorprenaline hydrochloride - Pandey, Rajesh Kumar; Upadhyay, Rajesh Kumar; Kumar, Pradeep (Arkivoc, 2006)
An efficient asymmetric synthesis of enantiomerically pure (R)-clorprenaline hydrochloride is described using Sharpless asymmetric dihydroxylation as the key step.

Eco-friendly synthesis of epichlorohydrin catalyzed by titanium silicate (TS-1) molecular sieve and hydrogen peroxide - Pandey, Rajesh Kumar; Kumar, Rajiv (Catalysis Communications, 2007)
In a mixed solvent system of acetonitrile and methanol, titanium silicate molecular sieve, TS-1, having MFI topology, efficiently catalyses the epoxidation of allyl chloride to the corresponding epichlorohydrin in excellent yields using dilute hydrogen peroxide (45%) as an oxidizing agent. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: allyl chloride; epichlorohydrin; epoxidation; heterogeneous catalysis; selectivity; titanium silicalite-1